Implementasi Metode Hazard Identification Risk Assessment And Risk Control Guna Peningkatan Keselamatan dan Kesehatan Karyawan di PT ABC - Alfina Fitri Damayanti; Nina Aini Mahbubah (Jurnal Serambi Engineering, 2021)
Zero accident was considered as the primary occupational health and safety value in manufacturing and service enterprises.  PT. ABC provided  electrical and instrument services, including a low-voltage installation, high-voltage installation and an instrument installation. This company is known to excellent electricity and instrument service providers across the country . Moreover, men’s power is used as a primary source to maintain  these kind  of services. Installation projects depend not only on the high working speed, but also on  high working  accuracy within  certain timeframes . As a result, work  accidents  have occurred with a classification varying from minor to fatal accidents.  The purpose of this research is to identify potential hazards to assess risk levels and  obtain recommendations for  preventing accident. The HIRARC method is employed as a research approach. This research is initiated through Hazard Identification, Risk Assessment and Risk Control.  This research identified that two hazards were classified as  extreme risk, three hazards as high- risk, eight hazards as moderate risk , and two hazards have been identified as low risk . Furthermore, a number of action lists have been suggested in order to minimize accident rates and finally the working conditions are designed to maintain zero accidents.